Cover Image, Volume 75, Issue 8. Issue 8 (5th July 2019) - Larue, Clayton T; Goley, Michael; Shi, Lei; Evdokimov, Artem G; Sparks, Oscar C; Ellis, Christine; Wollacott, Andrew M; Rydel, Timothy J; Halls, Coralie E; Van Scoyoc, Brook; Fu, Xiaoran; Nageotte, Jeffrey R; et al.
Abstract : The cover image is based on Research Article Development of enzymes for robust aryloxyphenoxypropionate and synthetic auxin herbicide tolerance traits in maize and soybean crops by Clayton T Larue et al., DOI:10.1002/ps.5393 X‐ray crystallography was used to solve the structure of FT enzymes (FT_T shown in both ribbons and space fill views). Abstract : The cover image is based on Research Article Development of enzymes for robust aryloxyphenoxypropionate and synthetic auxin herbicide tolerance traits in maize and soybean crops by Clayton T Larue et al., DOI:10.1002/ps.5393 X‐ray crystallography was used to solve the structure of FT enzymes (FT_T shown in both ribbons and space fill views).